Pathways Linking Parental Support to Adolescents’ Reading Proficiency: A Social Cognitive Theory Perspective - Chen, Xueliang; Hu, Jie (Frontiers in Psychology, 2021)
Parental support is essential to children’s motivation and academic functioning. However, few studies have investigated the pathways linking perceived parental support to children’s achievement in reading during adolescence. This study aims to fill this gap by systematically investigating the relationships among perceived support from parents, adolescents’ motivational beliefs and reading proficiency based on Bandura’s social cognitive theory. A range of motivational processes are explored, including self-efficacy, goals and values. Using the China sample from the Program of International Student Assessment (PISA) 2018, which includes 12,058 adolescents from 361 schools, this study proposed two competing models based on different accounts of self-efficacy beliefs. Multilevel path analysis is adopted as the analytic method. The results suggest that perceived support from parents has a statistically significant but negligible relationship with adolescents’ reading proficiency. However, this relationship is mediated by nuanced pathways such as self-efficacy beliefs, mastery goal orientation and reading enjoyment. Findings of this study provide evidence in support of the top-down theory of self-efficacy in the reading context and also contribute to a better understanding of the interactions between different motivational processes. Theoretical and practical implications of this study are discussed and suggestions for future research are offered.